The effect of leisure activity golf practice on motor imagery: an fMRI study in middle adulthood - Bezzola, Ladina; Mérillat, Susan; Jäncke, Lutz (Frontiers in Human Neuroscience, 2012)
Much is known about practice-induced plasticity of the motor system. But it is not clear how a physical training influences the mental rehearsal of the practiced task and its associated hemodynamic responses. In the present longitudinal study with two measurement time-points, we used the method of functional magnetic resonance imaging (fMRI) and a motor imagery task, in order to explore the dynamic neuro-functional changes induced by a highly complex physical training. The 11 golf novices between the age of 40 and 60 years practiced the motor training as leisure activity. Additionally, data from an age and sex-matched control group without golf training was collected. As a main result, we demonstrate that changes between the two measurement time-points were only found in the golf novice group. The golf novices showed a decrease in hemodynamic responses during the mental rehearsal of the golf swing in non-primary motor areas after the 40 h of golf practice. Thus, the results indicate that a complex physical leisure activity induces functional neuroplasticity in the seldom studied population of middle-aged adults, and that this effect is evident during mental rehearsal of the practiced task. This finding supports the idea that (a) a skill improvement is associated with a modified activation pattern in the associated neuronal network that can be identified during mental rehearsal of the practiced task, and that (b) a strict training protocol is not necessary to induce functional neuroplasticity.